Sobre humanos e máquinas: marcos epistêmicos, ontológicos e éticos para compreensão do ciborgue e aprendizagem humana na cultura digital - Oliveira, Daniel Figueiredo de (2017)
This work examines the ways in which cyborgs are constituted in the emerging dynamics of cyberculture and cyberspace, how cybernatives naturalize their technological needs, and the implications for these configurations for the field of human learning. In this context, the world of culture has become formalized as a second nature produced by human ingenuity, by way of an ecosystem of cybernetics, of hybrid humans constiututed through their symbiotic hyperconnectivity, that is to say, by the incorporation of the inorganic as a facilitator of a new existential status. In the context of these new configurations, the present research seeks to describe the relations between humans and intelligent machines, from the construction of conceptual foundations for grounding a philosophy of the cyborg and its configurations in human learning today. The guiding thesis of this investigation is that digital culture incorporates a cyborgian dynamics of production of cognitively altered human existence through the relations between humans and machines. Considering the complex aspects that have already been articulated and developed, the methodology used in this research took the concept of rhizome as a base on which to draw a conceptual cartography capable of elucidating the fundamental aspects of the territory of the relations between human beings and intelligent machines, focusing on aspects concerning the possibilities of learning. The analytic cartography was constructed based on the principle of multiplicity, which favored analysis by production or re-signification of the concepts that made up the study map once structures were constructed in the course of the emergence of chosen direcitons and rhizomatic inputs, always attent to possibilities of registered lines of escape. Ontological, ethical and epistemic lines were developed in order to situate the sociotechnical rationality that underlies modern and contemporary society. In the constructed theoretical equation, the educational and learning processes were taken to be the protagonists for the synthesis of the study. Our results outline the introductory elements for the emergence of a philosophy of the cyborg as the foundation of human learning. These elements give rise to a conception of cyborg practices understood as the epistemic, ontological and ethical practices of the reflexive movement provided by technology, digital networks and virtual reality which can be named cyberphilosophy.